On Generalizes Derivations And commutativity Of Centrally Prime Rings - Sulaiman, Neshtiman N. (Sulaimani Journal for Pure and Applied Sciences, 2016)
In this paper, we will study some important results relating to the concept of generalized derivation in centrally prime ring to be commutative.
Keywords: derivations; generalized derivations centrally prime rings